Epidemiology Of Non-Communicable Diseases In Pakistan: Are We On The Right Track? - admin; Mazen Alqera Atiq (ziauddin University, 2018)
With a population in excess of a 200 million coupled with an incommensurate allocation of resources, Pakistan has long fallen prey to the scourge of disease. Even more alarming is the insidious rise in the proportion of population 65 years or older; this group is particularly prone to non-communicable diseases (NCDs) which are estimated to contribute well over 50% to total deaths. This article describes the epidemiologic distribution of NCDs in Pakistan, with a special emphasis on the 4 main afflictions (Cardiovascular diseases, Cancers, Chronic Respiratory Diseases, and Diabetes) which together account for 36% of total deaths, a disconcerting figure considering that the approach to these conditions is largely preventive. In addition, an overview of current response strategies are provided in the hopes that future policy may be better guided